2018
DOI: 10.1007/s12039-017-1413-0
|View full text |Cite
|
Sign up to set email alerts
|

$$\mathrm{NiFe}_{2}\mathrm{O}_{4 }$$ NiFe 2 O 4 nanoparticles-decorated activated carbon nanocomposite based electrochemical sensor for selective detection of dopamine in presence of uric acid and ascorbic acid

Abstract: We propose an electrochemical sensor using NiFe 2 O 4 nanoparticles-decorated activated carbon (AC) nanocomposite for selective detection of dopamine (DA) in the presence of uric acid (UA) and ascorbic acid (AA). The nanocomposite was prepared by a simple hydrothermal method and the characterization was done using transmission electron microscope (TEM), scanning electron microscope (SEM), X-ray diffraction (XRD) patterns and Fourier transform infrared (FTIR) spectroscopy. The NiFe 2 O 4-AC-modified glassy carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Due to these diverse features, nanomaterials have got quite a bit of focus in recent years. To make considerable advances, researchers used a variety of nanomaterials, including polymers, metal nanoparticles, core shell nanostructures, alloys, the 2-D multilayer composites, carbon-based, and metal oxide nanocomposites [7][8]. In the development of blended compositional system applications, rare earth metal nanomaterials are exploited as functional materials.…”
Section: Introductionmentioning
confidence: 99%
“…Due to these diverse features, nanomaterials have got quite a bit of focus in recent years. To make considerable advances, researchers used a variety of nanomaterials, including polymers, metal nanoparticles, core shell nanostructures, alloys, the 2-D multilayer composites, carbon-based, and metal oxide nanocomposites [7][8]. In the development of blended compositional system applications, rare earth metal nanomaterials are exploited as functional materials.…”
Section: Introductionmentioning
confidence: 99%
“…Nickel ferrites have inverse pervoskite structure with trivalent cations occupying tetrahedral and octahedral sites and divalent cations occupying octahedral sites [21]. Nickel ferrites possess potential properties to be used in multiple applications like catalysis, drug delivery, electrochemical sensing and biosensing [22–25]. However pure metallic ferrites often show weak catalytic and sensing properties [26].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, using bimetallic nanoparticles modified electrodes has been described as promising route for the electrochemical AA sensor fabrication. [15][16][17][18][19] It has been reported that bimetallic nanoparticles such as PdNi, AuPt, AuAg, AgPt and PtNi, exhibit better electrochemical properties than their single-metal component. [19][20][21][22][23] Specifically, bimetallic CoPt NPs are believed to offer unprecedented benefits in catalysis by tuning the catalysts durability.…”
Section: Introductionmentioning
confidence: 99%